RETRACTED: Psychological aspects of the transition to a green economy - Prisniakova Liudmyla; Aharkov Oleh; Bukanov Hryhorii; Harets Nadiia; Tarasevych Inna (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001